Optimization of self-supported chromium-based catalyst for methane cracking - Lim, Teng Hui (Nanyang Technological University, 2021)
In the context of Singapore, our country is a renewable energy disadvantaged country as we have limited renewable energy sources that can be harvested in this tiny city-state. It is important to find an alternative and sustainable energy sources other than importing affordable green hydrogen from overseas. The interim solution to this would be obtaining hydrogen from methane cracking, which produces turquoise hydrogen without much harmful carbon dioxide being released to the atmosphere. Furthermore, the use of hydrogen energy system will result in lesser fossil fuels to be used as an energy source, thus lead to the decrease in the emission of greenhouse gases in our environment and would be a viable solution to tackle climate change. As such, the cracking of methane gas has been in high demand due to the production of carbon oxide free hydrogen. In this project, we will be optimizing the output level of carbon oxide free hydrogen using the chromium-based catalyst that will be doped with other metals, this will test the catalytic performance under reducing atmosphere of hydrogen and methane-containing gas. Samples were examined by field-emission scanning electron microscope (FESEM) to detect carbon deposition on the catalyst of the surface. It was found that chromium doped with nickel catalyst is more stable than the other dopants that were used. The carbon deposition on the catalyst have make it certain that these catalyst under methane reduction atmosphere will yield a remarkable result in both carbon and hydrogen.